Media Edukasi Interaktif Berbasis Web untuk Literasi Digital Dasawisma RW 01 Jatinegara - Romi Naufal Salam; Nandini Ladivina Sari; Ridho Arif Hidayat; Sugiyono Sugiyono; Mesra Betty Yel (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
The low level of digital literacy among grassroots communities, particularly the Dasawisma group within the Rukun Warga (RW) environment, limits the community's ability to use information technology effectively and safely. This Community Service Program aims to develop web-based interactive educational media as a digital literacy learning tool for Dasawisma members. The media was developed using the WordPress platform and the Waterfall development method. The implementation stages included user needs analysis, educational content design, interface design, WordPress installation and configuration, and system testing with users. The developed media takes the form of an interactive website that provides basic digital literacy materials, instructional videos, and evaluation quizzes accessible through various digital devices. The media trial was conducted with 20 members of Dasawisma RW 01 using a pretest and posttest method on a digital literacy quiz. The results showed an improvement in participants' understanding from 58% to 82% after using the media, representing an increase of 24%. This indicates that web-based educational media is effective in improving digital literacy among the Dasawisma community in RW 01, Jatinegara Sub-district, East Jakarta.